Directions of Development of Transport Networks and Traffic Engineering : 15th Scientific and Technical Conference "Transport Systems. Theory and Practice 2018", Katowice, Poland, September 17-19, 2018, Selected Papers /: 15th Scientific and Technical Conference "Transport Systems. Theory and Practice 2018", Katowice, Poland, September 17-19, 2018, Selected Papers. ([2019]) - Unknown
No abstract available